2012
DOI: 10.1097/gme.0b013e3182337150
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent pregnancy is associated with osteoporosis in postmenopausal women

Abstract: Adolescent pregnancy may be a predictor of osteoporosis in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 13 publications
1
26
1
2
Order By: Relevance
“…Further collection of that information in KNHANES is required. Inconsistent with the results of the present study, Cho et al [10] found that a history of pregnancy during adolescence is associated with an increased risk of osteoporosis in postmenopausal women. On the basis of this finding, it has been hypothesized that adolescent pregnancy may interfere with the formation of peak bone mass, which may increase the risk of osteoporosis during aging.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further collection of that information in KNHANES is required. Inconsistent with the results of the present study, Cho et al [10] found that a history of pregnancy during adolescence is associated with an increased risk of osteoporosis in postmenopausal women. On the basis of this finding, it has been hypothesized that adolescent pregnancy may interfere with the formation of peak bone mass, which may increase the risk of osteoporosis during aging.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, few studies have evaluated the long-term effects of maternal age on BMD. Although Cho et al [10] reported that a history of pregnancy during adolescence is associated with an increased risk of osteoporosis after menopause, it is unclear how delivery at an advanced maternal age affects BMD and osteoporosis after menopause. Pregnancies during adolescence and pregnancies at an advanced maternal age may result in unfavorable birth outcomes as well as maternal complications, including adverse bone health effects.…”
Section: Introductionmentioning
confidence: 97%
“…5 Previous studies have shown that the incidence of delivery during adolescence or at an advanced age was significantly higher in subjects with osteoporosis than in those without osteoporosis. 7,8 It was suggested that pregnancies during adolescence and pregnancies at an advanced maternal age may result in unfavorable birth outcomes as well as maternal complications, including adverse bone health effects. 7 However, the relationship between reproductive factors, including the history of pregnancy and delivery, and the number of teeth in postmenopausal women is unclear.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…However, 512 understanding the determinants of environmental variation in rates of maturation is of 513 interest from a medical perspective, because the onset of physical and physiological 514 adulthood is defined by an array of changes that have profound implications for many 515 aspects of the body's ability to function. Beyond that, the relationships between health 516 and age at menarche (Cho et al, 2012;Webb, Marshall, & Abel, 2011; Widen et al, 517 2012) suggest that understanding why individuals differ in the rate at which they enter 518 puberty may yield insights into the causes of inter-individual variation in health and 519 propensity to disease. 520…”
mentioning
confidence: 99%